2022
DOI: 10.1111/ppl.13663
|View full text |Cite
|
Sign up to set email alerts
|

Defining key metabolic roles in osmotic adjustment and ROS homeostasis in the recretohalophyte Karelinia caspia under salt stress

Abstract: The recretohalophyte Karelinia caspia is of forage and medical value and can remediate saline soils. We here assess the contribution of primary/secondary metabolism to osmotic adjustment and ROS homeostasis in Karelinia caspia under salt stress using multi‐omic approaches. Computerized phenomic assessments, tests for cellular osmotic changes and lipid peroxidation indicated that salt treatment had no detectable physical effect on K. caspia. Metabolomic analysis indicated that amino acids, saccharides, organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…Higher lipid peroxidation is a common phenomenon under salt stress caused by membrane injury, which leads to the production of a number of free oxygen radicals that ultimately disturbed the plants’ functioning and hence the metabolism . Under salt-induced oxidative stress, the excessive synthesis of ROS is controlled either by – OH and O 2 – or by molecular oxygen excitation (O 2 ) to form singlet oxygen. , The plants then abruptly activate their antioxidant potential system, which is principally regulated by SOD, POD, CAT, and APX antioxidant enzymes, in response to the excessive ROS production in order to scavenge the ROS and maintain the redox equilibrium, hence boosting plant development. In addition to enzyme antioxidants, nonenzymatic antioxidants including proline, phenolic, and flavonoids work as secondary metabolites to prevent oxidative stress from salt from causing oxidative damage. Similarly in the current study, the elevated levels of oxidative stress biomarkers were noticed in both Raphanus sativus L. genotypes, which were then reduced by the stimulation of an antioxidant potential system governed by both enzymatic and nonenzymatic antioxidants. Earlier reports also revealed that the higher activities of antioxidants were observed following saline stress in H.…”
Section: Discussionmentioning
confidence: 99%
“…Higher lipid peroxidation is a common phenomenon under salt stress caused by membrane injury, which leads to the production of a number of free oxygen radicals that ultimately disturbed the plants’ functioning and hence the metabolism . Under salt-induced oxidative stress, the excessive synthesis of ROS is controlled either by – OH and O 2 – or by molecular oxygen excitation (O 2 ) to form singlet oxygen. , The plants then abruptly activate their antioxidant potential system, which is principally regulated by SOD, POD, CAT, and APX antioxidant enzymes, in response to the excessive ROS production in order to scavenge the ROS and maintain the redox equilibrium, hence boosting plant development. In addition to enzyme antioxidants, nonenzymatic antioxidants including proline, phenolic, and flavonoids work as secondary metabolites to prevent oxidative stress from salt from causing oxidative damage. Similarly in the current study, the elevated levels of oxidative stress biomarkers were noticed in both Raphanus sativus L. genotypes, which were then reduced by the stimulation of an antioxidant potential system governed by both enzymatic and nonenzymatic antioxidants. Earlier reports also revealed that the higher activities of antioxidants were observed following saline stress in H.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was found that the saccharide metabolites associated with glycolysis increased significantly under salinity under L-S compared with CK (Figure 5B). As an important process of energy production, the increase of glycolysis metabolites could be linked to the enhanced production of reactive oxygen species (ROS) (Guo et al, 2022). Thus, an elevated accumulation of glycolysis metabolites might be coupled with the generation of ROS in S. europaea especially.…”
Section: Lipid Composition Is Involved In the Salt Resistance Of S Eu...mentioning
confidence: 99%
“…Similar observations have been reported in the halophytes Thellungiella halophila and Limonium latifolium in response to salt stress, suggesting that many changes in organic solute composition are predominantly controlled by constitutive developmental programs (Gong et al, 2005;Gagneul et al, 2007). The decrease of these metabolites might be accompanied by the suppression of energy production, implying that S. europaea adopted an energy conservation strategy from plant growth to the induction of protective mechanisms under salt stress; meanwhile, the inhibited TCA cycle flux might partially counteract ROS overproduction associated with glycolysis as a response of S. europaea to salt (Guo et al, 2022).…”
Section: Lipid Composition Is Involved In the Salt Resistance Of S Eu...mentioning
confidence: 99%
“…Further research demonstrated that overexpression of antioxidant enzyme genes such as CAT and POD regulated H 2 O 2 homeostasis and improved the tolerance to salt stress ( Zhou et al, 2018 ; Jin et al, 2019 ). Apart from the role of antioxidant enzymes in ROS scavenging, secondary metabolities such as chlorogenic acid, flavonoids, tocopherols, and polyamines play critical roles in the antioxidant mechanism ( Guo et al, 2022 ). For example, Jin and Daniell (2014) reported that the overexpression of γ-TMT increased the content of α-tocopherol, then decreased the production of ROS, thus improving the tolerance of tobacco to salinity.…”
Section: Introductionmentioning
confidence: 99%